Persisting IL-18 levels after COVID-19 correlate with markers of cardiovascular inflammation reflecting potential risk of CVDs development - Andrejčinová, Ivana; Blažková, Gabriela; Papatheodorou, Ioanna; Bendíčková, Kamila; Bosáková, Veronika; Skotáková, Monika; Panovský, Roman; Opatřil, Lukáš; Vymazal, Ondřej; Kovačovicová, Petra; Šrámek, Vladimír; Helán, Martin; et al. (Heliyon, 2024)
COVID-19 manifestation is associated with a strong immune system activation leading to inflammation and subsequently affecting the cardiovascular system. The objective of the study was to reveal possible interconnection between prolongated inflammation and the development or exacerbation of long-term cardiovascular complications after COVID-19. We investigated correlations between humoral and cellular immune system markers together with markers of cardiovascular inflammation/dysfunction during COVID-19 onset and subsequent recovery. We analyzed 22 hospitalized patients with severe COVID-19 within three timepoints (acute, 1 and 6 months after COVID-19) in order to track the impact of COVID-19 on the long-term decline of the cardiovascular system fitness and eventual development of CVDs. Among the cytokines dysregulated during COVID-19 changes, we showed significant correlations of IL-18 as a key driver of several pathophysiological changes with markers of cardiovascular inflammation/dysfunction. Our findings established novel immune-related markers, which can be used for the stratification of patients at high risk of CVDs for further therapy.
Keywords: COVID-19 long-term consequences; COVID-19; Inflammation; CVDs; IL-18